Invention/Erasure: Caste Identity Among the Weaving Community In Jaffna - Kirubalini, S. (My University, 2018)
In ancient Jaffna caste divisions were based on professions that people have been hereditarily engaged in. professions were assigned to every caste and the rights and duties were also allotted. The conditions after colonialism, the ethnic conflict, and displacement have overlooked caste discrimination rooted within the community, and as a result traditional industry transcends the caste – based social strata. Weaving in modern – day Jaffna is not restricted to any of the particular castes. Weaving has changed as a cottage industry under the control of the government. But weaving in primordial Jaffna provides the possibility to read the caste – communities, the social hierarchies, relationships between castes, and relationships with government, displacements, economy, and production systems. This research focuses on the social aspects of the weaving community in Jaffna. Particularly on the present plight of the community that was tied up with the weaving industry in the ancient past and became unemployed during the British rule. Specifically, how does the weaving community convey their caste identity? Or have they rediscovered their caste identity? Or do they hide it? Or have they forgotten it? This research examines these questions the platform of remaining religious rituals, names of their villages and roads, names of common places, and some individual experiences.